WORKSHOP PENYUSUNAN MEDIA PEMBELAJARAN BERBASIS PENDIDIKAN INKLUSIF DI GUGUS 1 KEC. KOPANG KAB. LOMBOK TENGAH - Setiawan, Heri; Karnia, Ari; Ahmad, Ahmad; Saputra, Heri Hadi; Oktaviyanti, Itsna; Affandi, Lalu Hamdian; Ermiana, Ida; Witono, A. Hari; Hakim, Mansur (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2024)
Education is one of human efforts to improve the dignity and standard of life. This improvement effort is carried out by developing competence, knowledge, attitudes, and the need for education which is the right of all citizens, and this is guaranteed by the 1945 Constitution. Implementing inclusive education is one way to make this happen. District Government Central Lombok, through the Department of Education and Culture, in collaboration with Innovation Indonesia and FKIP UNRAM, is holding a series of workshops, one of which is strengthening teacher competency in selecting and utilizing inclusive education-based learning media. The workshop was held in Gugus 1 Kec. Kopang with a total of 8 elementary schools and 32 lower class teachers as participants. Activities were carried out in October 2019 through workshops and field assistance. The results of the activity show that the objective of the activity was achieved, namely strengthening the competency of elementary school teachers in selecting and utilizing inclusive education-based media in the classroom. The pretest and posttest results show that the teacher's conceptual understanding has increased.